Peran Guru Dalam Membangun Karakter Wirausaha pada Mata Pelajaran Ekonomi Di Kota Padang - Sri Arita; Susi Evanita; Rita Syofyan (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2019)
The purpose of this study was to determine the teacher's role in make entrepreneurial character in Economics. Entrepreneurial character is something that must be developed in education. The young generation is expected to create broad jobs in the community. The formation of these characters can be done in learning through several values or indicators and adopted into economic subjects. The indicator is the locus of control, willing to bear the risk, creativity and the ability to build good social relationships. This research is a descriptive study involving MGMP of Economic Subjects in Padang City, based on the results of MGMP teacher studies the city of Padang has developed entrepreneurial character in economic subjects, but still needs to be improved in several indicators, such as creativity and building good social relations.